CSR DISCLOSURE DAN EARNING RESPONSE COEFFICIENT - Agung Prasetyo Nugroho Wicaksono (AKUNTABEL, 2017)
The aim of this study to examined the effect of corporate social responsibility information disclosed in the company's annual report with Earning Response Coefficient. Data of this research is secondary data from annual report listed on Indonesia Stock Exchange with 51 listed companies in period 2015 by categories from European Bank and The State of NSW and The Environment Protection Authority (EPA). Method of analysis used linear reggession. The empirical results of this paper showed that the level of CSR disclosure affected the ERC. This result indicate that investor rate the CSR disclosure for investment decisions.Keywords: Corporate Social Responsibility Disclosure, Earnings Response Coefficient